Pola Komunikasi Humas PMI di Masa Pandemi - Arshky Muntazmahal; Mohamad Subur Drajat (Bandung Conference Series: Public Relations, 2022)
Abstract. The Covid-19 outbreak is a very big problem for the community because they cannot carry out their usual activities and are forced to stay at home. Covid-19 requires social distancing, not crowding, and maintaining personal and environmental hygiene. Therefore, the public needs information regarding the prevention of Covid-19. PMI as a health organization contributes to the handling of the Pandemic in Indonesia. In its communication activities, PMI seeks to provide information on the prevention of Covid-19 to the public. This study aims to determine PMI's communication activities with the community during the pandemic, to find out the use of Communication Media, to know about PMI's Public Relations Information Management, and to know PMI's PR in carrying out interactions with the community. The research method used in this study is qualitative with a Case Study approach, and Constructivism Paradigm. The data collection techniques used were in-depth interviews, observations, literature studies, and documentation with data reduction analysis techniques. The results of the research in this study Public Relations of PMI used communication media in conveying information regarding the prevention of Covid-19 to the public. PMI stakeholders take advantage by using social media, print media, and electronic media. PMI manages Covid-19 response messages by obtaining information from credible sources, aligning information, classifying messages, and organizing messages. PMI Public Relations conducts interactions with the community through Customer Service, through social media and obtains feedback from interactions with the community. In PMI Bandung City's PR communication activities, use time in total, interact with the community, and communicate instrumentally. Abstrak. Wabah Covid-19 menjadi masalah yang sangat besar bagi masyarakat karena tidak bisa beraktivitas seperti biasanya dan terpaksa harus berdiam diri di rumah. Covid-19 mengharuskan untuk menjaga jarak sosial, tidak berkerumun, dan menjaga kebersihan diri maupun lingkungan. Maka dari itu masyarakat membutuhkan informasi mengenai penanggulangan Covid-19. PMI sebagai sebuah organisasi kesehatan berkontribusi dalam penanganan Pandemi di Indonesia. Dalam aktivitas komunikasinya PMI berupaya memberikan informasi penanggulangan Covid-19 kepada Masyarakat. Penelitian ini bertujuan untuk mengetahui aktivitas komunikasi PMI dengan masyarakat di masa pandemi, mengetahui pemanfaatan Media Komunikasi, mengetahui mengenai Pengelolaan Informasi Humas PMI, dan mengetahui Humas PMI dalam melaksanakan interaksi dengan masyarakat. Metode penelitian yang digunakan pada penelitian ini kualitatif dengan pendekatan Studi Kasus, dan Paradigma Konstruktivisme. Teknik pengumpulan data yang dilakukan adalah wawancara mendalam, observasi, studi pustaka, dan dokumentasi dengan teknik analisis reduksi data. Hasil penelitian pada penelitian ini Humas PMI memanfaatkan media komunikasi dalam menyampaikan informasi mengenai penanggulangan Covid-19 kepada masyarakat. Stakeholder PMI memanfaatkan dengan menggunakan media sosial, media cetak, dan media elektronik. PMI mengelola pesan penanggulangan Covid-19 dengan memperoleh informasi dari sumber yang kredibel, menyelaraskan informasi, klasifikasi pesan, dan mengoragnisir pesan. Humas PMI melaksanakan interaksi dengan masyarakat melalui Customer Service, melalui media sosial dan memperoleh umpan balik dari interaksi dengan masyarakat. Pada aktivitas komunikasi Humas PMI Kota Bandung memanfaatkan waktu secara total, interaksi dengan masyarakat, dan melakukan komunikasi secara instrumental.